Penyelesaian Sengketa oleh Majelis Adat Setikar Kampung di Kabupaten Aceh Tamiang dan Kedudukannya dalam Sistem Peradilan Indonesia - Muharrir Muharrir; Muhammad Nahyan Zulfikar; Jefrie Maulana (Prodi Ilmu Hukum, Universitas Teuku Umar, 2022)
Settlement of disputes between residents in Aceh Tamiang Regency was organized by the Setikar Village Council (MDSK) as a village deliberation body, which was later better known by the community through mediation through village traditional apparatus. This study aims to find out and explain how the procedures for resolving disputes between communities by MDSK, and analyze the legal certainty of dispute resolution between communities by MDSK in the Indonesian Judicial system. The research method of this study is normative juridical research by examining aspects of legal certainty in dispute resolution by the Aceh Tamiang District MDSK in the Indonesian justice system. The legal materials used consist of primary, secondary and tertiary legal materials. The approach taken in this research is the approach to legislation and the approach to the principle of legal certainty. The research data will be analyzed qualitatively in accordance with the legislation and conformity with the principle of legal certainty. The results of the study indicate that out-of-court dispute resolution in Aceh Tamiang District is organized by MDSK. The dispute resolution process is carried out by examining initial data related to the subject of the dispute, examining documentary evidence and adjusting it in the field, then making decisions by deliberation and consensus. Dispute resolution by MDSK has not met the principle of legal certainty. Because, MDSK does not have legality as a mediation forum and is not recognized as a mediator as regulated in Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court. Then, there are no implementing regulations in the form of guidelines for dispute resolution through MDSK, standard rules for implementation procedures and dispute resolution procedures.